Injection augmentation and endoscopic repair of type 1 laryngeal clefts: development of a management algorithm - Andre Isaac; Orysya Svystun; Wendy Johannsen; Hamdy El-Hakim (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objectives To describe indications for injection augmentation (IA), endoscopic repair (ER) and conservative methods for the management of type 1 laryngeal cleft (LC1) and propose a management algorithm. We also aimed to compare success of IA and ER and determine independent predictors of treatment failure. Methods Retrospective study of patients diagnosed with LC1 at a Pediatric Otolaryngology referral centre between 2004 and 2016. All had pre-operative instrumental swallowing evaluation (VFSS/FEES), and were managed with a combination of conservative measures, IA and/or ER. We collected demographics, symptoms, comorbidities, VFSS/FEES results, and operative details. The primary outcome was symptom resolution by parental report. The secondary outcome was predictors of treatment failure. Results 88 patients were included in the analysis, with mean age 26 ± 25 months. Most presented with choking events (68%) or recurrent pneumonias (48%). In total, there were 55 IA performed and 45 ER. Of the patients who received IA, 19 required subsequent ER. 95% had symptom improvement, 67% had complete resolution. IA had a 56% long-term success rate, whereas that for ER was 85%. Tube feeding at initial evaluation was an independent predictor of treatment failure (HR 11.33 [1.51–84.97], p = 0.018). Conclusions LC1 can be effectively managed with a combination of IA and ER with favorable results. Failure to respond to IA does not preclude ER, and both have their role in management. Patients who are tube fed have a higher probability of treatment failure. We propose a management algorithm that includes reasoning for conservative approaches, and reduces exposure to general anesthesia.